Global capital, uneven development and national difference: Critical reflections on the specificity of accumulation in Latin America - Fitzsimons, Alejandro Luis (2018)
A recent Special Issue in this journal devoted its pages to discuss the varied forms of capitalist development in different countries and regions across the globe. Specifically, the contributions offered a critical assessment of the hegemonic ‘neo-institutionalist’ approach to the study of national diversity of capitalism, with particular focus on the ‘varieties of capitalism’ approach. This article critically engages with the different alternatives to the varieties of capitalism approach that were put forward and shows that these other perspectives also fall short of providing a convincing framework to address the problematique of national or regional particularities as posed in the debate. In order to offer a more solid explanation of the phenomenon of ‘capitalist variety’, the article draws upon Marx’s fundamental insight into the determination of capital as a materialised social relation which becomes the immediate alienated subject of the organisation of the process of social life and also moves some way beyond it so as to cast fresh light on global transformation and uneven development in recent decades. More concretely, the article further submits that the specificity of the Latin American ‘variety of capitalism’ must be grounded in the constitution and dynamics of the international division of labour which results from the underlying essential unity of the production of relative surplus value on a world scale by the global total social capital. In other words, we grasp the emergence of national specificities as the immanent result of the global unfolding of the ‘law of value’.